Hypertension: The Cardiovascular Risk Continuum - IW Wita (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Hypertension is established modifiable risk factor for cardiovascular diseases (CVD) and should .....